1992
DOI: 10.1136/bmj.304.6843.1668-a
|View full text |Cite
|
Sign up to set email alerts
|

Regular balloon inflation for patients with chronic bronchitis: a randomised controlled trial.

Abstract: Preterm labour continues to complicate a substantial number of pregnancies, and preterm delivery accounts for most early neonatal deaths not due to congenital abnormalities.' Ritodrine hydrochloride, a 13 sympathomimetic agent with predominant effects on 0 receptors such as those of the uterus,2 is effective in suppressing premature uterine contractions.2 We describe six pregnant women given ritodrine hydrochloride who developed swelling of the salivary glands with hypersecretion of amylase. Patients and resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1993
1993
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 3 publications
0
6
0
Order By: Relevance
“…If the patient's home had no stairs or he/she was assessed as unsafe performing this exercise, unweighted straight‐leg‐raising (lying) and knee extension (sitting) were substituted. Inflating party balloons to the size of melons. This has been shown to improve dyspnea and well‐being in young COPD patients …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…If the patient's home had no stairs or he/she was assessed as unsafe performing this exercise, unweighted straight‐leg‐raising (lying) and knee extension (sitting) were substituted. Inflating party balloons to the size of melons. This has been shown to improve dyspnea and well‐being in young COPD patients …”
Section: Methodsmentioning
confidence: 99%
“…Inflating party balloons to the size of melons. This has been shown to improve dyspnea and well‐being in young COPD patients …”
Section: Methodsmentioning
confidence: 99%
“…Here the technology can again be portable and even cheaper than inspiratory resistive techniques -inflating balloons at home is a low-cost method with high patient acceptability, and a beneficial effect upon breathlessness and well-being in older patients. 30 The only study so far of this technique was small and its results have yet to be replicated by others. It is certainly worthy of further study and may be particularly appropriate to the elderly.…”
Section: The Clinical Application Of Muscletraining Techniquesmentioning
confidence: 95%
“…At the beginning and end of the study, each subject was assessed on three outcome measures: distance walked in six minutes, overall sense of well-being, and self-assessment of breathlessness. At the end of the study, the balloon group showed a significant improvement in breathlessness and slight but no significant improvements in walking distance and well-being [7].…”
Section: Introductionmentioning
confidence: 96%
“…Data was collected using observation and interviewing method focusing on the improvement in dyspnoeic state among patients with lower respiratory tract disorder. The data was collected from wards for a period of two weeks [7,10].…”
Section: Procedures For Data Collectionmentioning
confidence: 99%